Optimization of cultivation conditions of Candida catenulata in synthesizing acidic sophorolipid - F. Amiri; A. R. Habibi; M. M. Nourouzpour (Iranian Journal of Chemical Engineering)
The application of the agro-industrial waste as the feedstock helps to decrease the operational cost of the fermentation process. Soapstock is a by-product of the vegetable oil refinery and enriched with fatty acids including linoleic acid which has a high potential application in the production of biosurfactants. In this study, a dual carbon source system, including glucose and free fatty acids recovered from a sunflower soapstock, was used for the synthesis of sophorolipid (SL) by Candida catenulata. The production of SL showed a major dependence on the initial carbon sources and the concentration of urea as the nitrogen source. The inoculum size was another influential factor in the fermentation process. The optimization of these factors was evaluated by the one-factor-at-a-time and the response surface methodology (RSM). The one-factor-at-a-time approach gained the best SL productivity (Y1) of about 52.08 mg L-1 h-1 and SL-to-biomass yield (Y2) of 712 mgSL gcell-1 at the inoculum size of 4% vv-1, 100 g L-1 of glucose, 80 g L-1 of soapstock, and 7.5 g L-1 of urea. While the RSM, due to considering interactional effects of the factors, obtained the best condition at 100 g L-1 of glucose, 100 g L-1 of the soapstock, 9.3 g L-1 of urea, and an inoculum size of 6.3% vv-1 with the Y1 and Y1 values of about 58.10 mg L-1 h-1 and 713 mgSL gcell-1, respectively. The characterization of the produced SLs by the GC-MS analysis indicated that a di-acylated C16:1 acidic sophorolipid with an m/z ratio of 679 amu was the main product.